2017
DOI: 10.1002/2017ja023951
|View full text |Cite
|
Sign up to set email alerts
|

Observation and simulation of the ionosphere disturbance waves triggered by rocket exhausts

Abstract: Observations and theoretical modeling of the ionospheric disturbance waves generated by rocket launches are investigated. During the rocket passage, time rate change of total electron content (rTEC) enhancement with the V‐shape shock wave signature is commonly observed, followed by acoustic wave disturbances and region of negative rTEC centered along the trajectory. Ten to fifteen min after the rocket passage, delayed disturbance waves appeared and propagated along direction normal to the V‐shape wavefronts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…Various wave periods and horizontal phase velocities of rocket‐induced SAWs are reported in previous literature by Calais and Minster (), Bowling et al (), Ding et al (), Lin et al (), Lin, Shen, et al (), and Lin, Chen, et al (). The wave period (~10.28 min) in this study is longer than the previous events listed in Table , but it is still within the acoustic cutoff period shown in Figure b.…”
Section: Observations and Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Various wave periods and horizontal phase velocities of rocket‐induced SAWs are reported in previous literature by Calais and Minster (), Bowling et al (), Ding et al (), Lin et al (), Lin, Shen, et al (), and Lin, Chen, et al (). The wave period (~10.28 min) in this study is longer than the previous events listed in Table , but it is still within the acoustic cutoff period shown in Figure b.…”
Section: Observations and Discussionmentioning
confidence: 69%
“…Theoretical studies and numerical model simulations on the effect of plume‐released reactive molecules in the ionosphere have been conducted (Bernhardt et al, ; Mendillo & Forbes, ). The passage of rocket‐triggered traveling ionospheric disturbances (TIDs) associated with the shock acoustic waves (SAWs) were investigated and simulated (Arendt, ; Afraimovich, Kosogorov, & Plotnikov, ; Calais & Minster, ; Donn et al, ; Noble, ; Kakinami et al, ; Lin et al, , Lin, Chen, et al, ). Kakinami et al () observed the V‐shape SAWs in GPS total electron content (TEC) triggered by a missile launch from North Korea on 12 December 2012 by using the dense regional GPS networks in Japan, Korea, and Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (1994) examined the TEC observation and reported the initial positive pressure perturbation induced by a space shuttle. Lin et al (2017) added additional energy in the energy equation of the model from Matsumura et al (2011) and simulated the shock wave induced by a rocket. The simulation of a rocketinduced shock wave is different from the simulation of a localized heat sink (moon shadow) traveling Geophysical Research Letters 10.1002/2017GL075926 through a gravitationally stratified atmosphere with a supersonic speed.…”
Section: Discussionmentioning
confidence: 99%
“…Using the above detection techniques, changes of the TID are detected by analyzing the ionospheric parameters, including total electron content, and electron density, etc. [3][4][5][6][7][8]. Studies on large meteor explosions in the lower atmosphere are rare, and the current studies mainly focus on the ionospheric disturbances caused by the 2013 Chelyabinsk meteor explosion.…”
Section: Introductionmentioning
confidence: 99%